Pelatihan Penelitian Tindakan Kelas Bagi Guru-Guru Di Larantuka - Hendrik AE Lao; Jonathan Leobisa; Andrian Wira Syahputra (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2024)
This training aims to provide teachers with an understanding of the importance of classroom action research, as an effort to improve the process and quality of learning in schools, as well as the importance of writing classroom action research itself for the teacher's career advancement in terms of proposing rank and career path. This activity was carried out in the form of classroom action research (PTK) writing training which lasted for 2 (two) days starting December 8-9 2021. The material presented consisted of 2 (two) main themes, namely the basic concepts of classroom action research and practical writing exercises. classroom action research. The number of participants who participated in the training was 100 teachers (multi-religious). The training material delivery method consists of lectures, question and answer, discussion, and direct practice in making classroom action research proposals. The training results showed that participants' understanding and mastery of PTK material had increased after attending the training compared to before. Additionally, training participants already have the skills and ability to make Class Action Research Proposals (CAR) and be highly motivated to participate in training activities.